A promising material for thermal barrier coating: Pyrochlore-related compound Sm2FeTaO7. (May 2018) - Yang, Jun; Han, Yi; Shahid, Muhammad; Pan, Wei; Zhao, Meng; Wu, Wangjie; Wan, Chunlei
Abstract: Pyrochlore-related compound Sm2 FeTaO7 was synthesized and investigated. It is shown that the thermal conductivity values are approximately half of the Yttria-Stabilized Zirconia (YSZ) over the temperature range of 25–1000 °C. Especially, thermal conductivity at high temperature is close to that of minimum thermal conductivity, as predicted by theoretical investigation, signifying better heat insulation capabilities. Considering lower Young modulus, improved fracture toughness, and better high-temperature phase stability, Sm2 FeTaO7 compound can be a promising material for thermal insulating applications, such as thermal barrier coatings. Graphical abstract: Unlabelled Image